2002
DOI: 10.1111/j.1365-2621.2002.tb09480.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cooking on the Crispness of Cassava Chips

Abstract: Technology for the production of edible cassava chips was studied, using pretreatments such as cooking and partial drying to improve chip crispness. Different cassava varieties and types of cooking, such as boiling water and steam, were also investigated. The effects of such treatments were evaluated on chip friability criteria by using the Texture Analyzer TA.XT2, as well as affective tests for sensorial measurement. A significant correlation (-0.90592; p # 0.05) was found between friability and sensory accep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0
5

Year Published

2003
2003
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 21 publications
2
8
0
5
Order By: Relevance
“…Dehydrated chips made with the BRS Jari variety and hybrid 2003 14-11 had highest average for flavor attribute and did not differ (p>0.05) on the crispness and overall acceptance and classified between "like slightly" and "like moderately". The acceptance values obtained in this work for the BRS Jari genotypes and hybrid 2003 14-11 are similar to those reported by Grizotto and Menezes (2002) for cassava chips elaborated with IAC Mantiqueira and IAC 576.70 varieties, receiving grades between 4.9 and 6.3 for the global acceptance and appearance attributes.…”
Section: Resultssupporting
confidence: 74%
“…Dehydrated chips made with the BRS Jari variety and hybrid 2003 14-11 had highest average for flavor attribute and did not differ (p>0.05) on the crispness and overall acceptance and classified between "like slightly" and "like moderately". The acceptance values obtained in this work for the BRS Jari genotypes and hybrid 2003 14-11 are similar to those reported by Grizotto and Menezes (2002) for cassava chips elaborated with IAC Mantiqueira and IAC 576.70 varieties, receiving grades between 4.9 and 6.3 for the global acceptance and appearance attributes.…”
Section: Resultssupporting
confidence: 74%
“…Grizotto and De Menezes, 2002 showed that crispness and friability were quality criteria for fried cassava. In addition Vitrac et al, 2001 reported that crisp quality was depending on oil content, colour and texture for the same dehydration level.…”
Section: Fried Cassavamentioning
confidence: 99%
“…This instrument has been used in a diverse range of texture analysis applications, including compressibility of fish (Arvanitoyannis, Tsitsika, & Panagiotaki, 2005), crispness of cassava chips (Grizotto & Menezes, 2002), mechanical characterization of instant coffee agglomerates (Gerhards, Ulbricht, & Peleg, 1998), texture analysis of fried tortilla chips (Kawas & Moreira, 2001), and many more. A more thorough list of publications is provided on the website of Stable Micro Systems Ltd. (Stable Micro Systems Ltd., 2006).…”
Section: At-line Analysis (Visual Blister Level Appraisal and Mechanimentioning
confidence: 99%